The Structure of Ordered Mesoporous Materials Synthesized from Aluminum Phyllosilicate Clay (Bentonite) - Malgorzata Zienkiewicz-Strzalka; Stanislaw Pikus; Malgorzata Skibinska; Magdalena Blachnio; Anna Derylo-Marczewska (Molecules, 2023)
This paper reports the synthesis and structural analysis of mesoporous silica materials with the use of aluminum phyllosilicate clay (bentonite) as an alternative silica source. In the proposed synthesis, bentonite, as natural aluminosilicate, was used instead of commercially available and quite expensive tetraethyl orthosilicate (TEOS) silica source. The objective of the research study was to determine the effect of aluminum loading in the mesoporous silica body for ordering structure, porosity, and potential sorption capacity to thorium ions. The unique direction developed in this procedure is focused on preparing advanced materials from natural sources with their own desired functionality and general availability. The applied procedure based on the classic, one-step synthesis of SBA-15 silicates was modified by gradually increasing the bentonite amount with simultaneous reduction of the TEOS content. The structural and morphological characterization, as well as evaluation of the porous structure of the obtained materials, was performed using powder wide-angle X-ray diffraction (XRD), small-angle scattering (SAXS), transmission and scanning electron microscopy (TEM, SEM), low-temperature nitrogen adsorption–desorption methods and potentiometric titration. The new, cost-effective composites for the removal of Th(IV) ions are proposed. The synergistic effect of expanding the porous surface using bentonite as a silica precursor and the presence of thorium-binding groups (such as Al2O3) is indicated.